National culture dimension of power distance in the Baltic States - Luptáková, Stanislava; Vargic, Branislav; Kincel, Ivan (Journal of Business Economics and Management, 2005)
The paper presents a calculation for the values of power distance index in the countries of Latvia, Lithuania and Estonia using a mathematical model that is based on the correlations between power distance index values of the original research conducted by Geert Hofstede and macroeconomic indicators. Following, the paper presents implications of the found power distance indexes on managerial practices in the local organizations as well as on transferability of the managerial practices of multinationals presented in the region onto the local workforce. First published online: 14 Oct 2010